PENGGUNAAN MODEL SCRAMBLE UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS IV - Juardi, Juardi; Suryani, Suryani; Syamsiati, Syamsiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrackThe title of this research is the use of scramble model to improve student learning activity. The method used in this research is descriptive method, the type of research is classroom action research (Classroom Action Research) and the nature of research that is collaborative. Data collecting technique used is direct observation technique. This research was conducted for three cycles with the results obtained that is 1) the ability of teachers in planning learning by using a model of scramble from cycle I ie 3.62, cycle II 3.74, cycle III 3.92. 2) the ability of teachers in the implementation of learning using scramble model from cycle I is 3.26, cycle II 3.55, cycle III 3.83. 3) student learning activity using scramble model starting from cycle I that is 49,52%, cycle II 69,52% and cycle III 87,61%. With the results obtained show that using the model scramble in learning Citizenship Education can improve the learning activities of fourth graders Elementary School 11 Pontianak CityÂ Keywords : Learning activities, Scramble